802 CONCURRENT PATHOLOGIES OBSERVED IN OLDER ADULTS WITH COVID-19 INFECTION. (8th March 2022) - Murphy, C; Hartop, K; Aggrey, K; Bilan, J; Lumsden, J; Colquhoun, K; Quinn, T
Abstract: Introduction: This study aimed to look at the effect of frailty and multi morbidity on short-term outcomes in patients diagnosed with COVID-19 in a hospital setting, looking specifically at the variety of concurrent pathologies diagnosed during their admission and how these affected the course of their illness and mortality. Methods: The study took place at Glasgow Royal Infirmary. We retrospectively collected data from 280 patients who were admitted to the medicine for the elderly department between the 1st October and 1st December 2020 and diagnosed with COVID-19. Results: In this cohort, 65% of older adults in hospital with COVID-19 had their admissions complicated by concurrent pathologies; most commonly delirium, acute kidney injury and pulmonary embolism, also increasing mortality in this group. It was also found that 39% of patients in this group had co-pathologies that were not necessarily associated with COVID-19 disease, for example AKI, AF and stroke/TIA. 35% of older adults in this group had no concurrent medical diagnoses during their admission, however this did not correlate with reduced mortality in this group. Conclusion: The data highlights the vulnerability of older adults with COVID-19 infection making them more susceptible to concurrent disease and contributing to further morbidity and mortality. We also found a large number of patients had co-pathologies not associated with COVID-19 disease, highlighting the importance of considering other diagnoses in frail elderly patients.